Role of capsule in adherence of Haemophilus influenzae type b to human buccal epithelial cells. - LiPuma, J J (1987)
The role of capsule in the adherence of Haemophilus influenzae type b to human epithelial cells in vitro was examined. A group of 30 nonadherent isolates did not differ in degree of encapsulation compared with their respective adherent variants. Furthermore, capsule-deficient mutants of both nonadherent and adherent variants did not differ significantly in degree of adherence compared with their respective encapsulated parents. These data indicate that capsule does not significantly influence the adherence of H. influenzae type b to human epithelial cells.